Semiotic Analysis of Body Shaming Communication in True Beauty Film (Cinematology: Journal Anthology of Film and Television Studies, 2025)
The film, in addition to containing elements of entertainment, also encompasses aspects such as education for the audience. Films often portray stories that reflect real-life societal experiences. They also include both verbal and non-verbal communication elements related to body shaming. Films are typically enjoyed not only as entertainment but also as sources of life lessons. Through this, viewers can understand the communication that occurs within those two aspects. In the film True Beauty, the method used in this study is qualitative. This research applies a descriptive approach to explain the events presented. The author explores incidents related to body shaming depicted in True Beauty, along with the potential mental health risks it causes, such as: developing insecurity, social withdrawal, hindrance to self-development, engaging in extreme measures to alter one’s physical appearance, and even committing self-harm or suicide. Society often equates beauty with physical appearance; however, this drama presents a contrast between outer beauty and inner beauty. Recognizing and being grateful for both the strengths and weaknesses of oneself and others is one of the most valuable lessons that can be learned from this film.